EXPERIENCE ORIENTED EXPLOITATION OF THE NATURAL AND CULTURAL RESOURCES OF MOSONMAGYARÓVÁR AND ITS SURROUNDINGS, A HUNGARIAN MICRO-REGION - HUSZ, Anikó (PEOPLE: International Journal of Social Sciences, 2017)
The main target of my research is to expose the tourist and free time possibilities of the region and to emphasize the importance of the connection between these two components. I would like to prove that it is the experience orientated way of thinking which connects the service providers and which we have to strive for. I would enhance that the offer of a leisure or tourist establishment can supply appealing programmes, services for both target groups (local and tourist guests).The tourist supply of the region is appealing for the locals as well, but they consider it as free time possibilities.It is significant to develop an identity image among the local population. The local identity strengthens, promotes the improvement and development of tourism in the region. I presume that the local people too can identify themselves with the spots, buildings which attract the visitors who come to the region.